ONCO-EPIDEMIOLOGICAL CHARACTERISTICS OF DISEASES OF THE FEMALE BREAST - Xolmamatova Larisa Xakberdiyevna; Choriyev Beruniy Akbarovich (Scholar Express Journals, 2023)
This article will cover in more detail the reasons for the high incidence of breast diseases among women, as well as the tendency to develop breast diseases as a result of risk factors. The features of the reproductive state of female military personnel depend on the following factors: not breastfeeding a child, late pregnancy, abortion, living in various climatic and field conditions. There is also a significant increase in gynecological diseases among female soldiers and family members of military personnel. Therefore, for female soldiers, the need to maintain reproductive health is an additional challenge.
Keywords: malignant tumor; reproductive system; breast cancer; mastopathy